Edukasi Bahaya Gempa Bumi di Sdn 51 Maluku Tengah, Dusun Wainuru, Desa Liang - Fauzan A. Sangadji (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
Liang Village in Central Maluku district, Maluku province, was the village that was most affected by successive earthquakes in 2019. The location of the point of the earthquake which was near caused the Liang village to suffer a lot of damage to buildings. Damage to this building can cause the ceiling and walls of the building to collapse, so it is very dangerous for the community. The purpose of this service is that after carrying out this service, activity participants can understand the dangers of earthquakes, the causes of earthquakes, the disasters that follow earthquakes and rescue actions. This educational activity is one of a series of civil engineering community service activities at Pattimura University. This education is carried out by conducting live presentations and showing video material that will be delivered to teachers and students of SDN 51 Central Maluku. The results of this education can be seen from the enthusiasm of students who can answer the speaker's questions from the material that has been provided. After this educational activity, students and teachers at SDN 51 Central Maluku, Dusun Wainuru, are expected to be able to understand how to take preventive and rescue measures when an earthquake occurs in the future.